Multiparametric prostate magnetic resonance imaging in the evaluation of prostate cancer. (23rd November 2015) - Turkbey, Baris; Brown, Anna M.; Sankineni, Sandeep; Wood, Bradford J.; Pinto, Peter A.; Choyke, Peter L.
Abstract : Imaging has traditionally played a minor role in the diagnosis and staging of prostate cancer. However, recent controversies generated by the use of prostate‐specific antigen (PSA) screening followed by random biopsy have encouraged the development of new imaging methods for prostate cancer. Multiparametric magnetic resonance imaging (mpMRI) has emerged as the imaging method best able to detect clinically significant prostate cancers and to guide biopsies. Here, the authors explain what mpMRI is and how it is used clinically, especially with regard to high‐risk populations, and we discuss the impact of mpMRI on treatment decisions for men with prostate cancer.CA Cancer J Clin 2016;66:326‐336. © 2015 American Cancer Society